2007
DOI: 10.1002/ibd.20029
|View full text |Cite
|
Sign up to set email alerts
|

Update on the incidence and prevalence of Crohnʼs disease and ulcerative colitis in Olmsted County, Minnesota, 1940–2000

Abstract: Although incidence rates of CD and UC increased after 1940, they have remained stable over the past 30 years. Since 1991 the prevalence of UC decreased by 7%, and the prevalence of CD increased about 31%. Extrapolating these figures to US Census data, there were approximately 1.1 million people with inflammatory bowel disease in the US in 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
234
4
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 553 publications
(260 citation statements)
references
References 43 publications
(59 reference statements)
15
234
4
7
Order By: Relevance
“…According to United States estimates for CD, incidence varies between 6 and 8 per 100,000 inhabitants, with a prevalence of 100 to 200 per 100,000 inhabitants. In the case of UC, the incidence in that country ranges between 9 and 12, with a prevalence of 205 to 240 per 100,000 inhabitants (15,17,22) . Studies have shown higher rates of incidence of IBD in developing countries, including Brazil (8,34,38) .…”
Section: Introductionmentioning
confidence: 99%
“…According to United States estimates for CD, incidence varies between 6 and 8 per 100,000 inhabitants, with a prevalence of 100 to 200 per 100,000 inhabitants. In the case of UC, the incidence in that country ranges between 9 and 12, with a prevalence of 205 to 240 per 100,000 inhabitants (15,17,22) . Studies have shown higher rates of incidence of IBD in developing countries, including Brazil (8,34,38) .…”
Section: Introductionmentioning
confidence: 99%
“…The population prevalence of UC and CD are between 150 and 250 per 100,000 people. [1][2][3][4][5][6] Patients present with symptoms such as abdominal pain, change in bowel habit, and rectal bleeding. 7, 8 However, these symptoms are common in patients who do not have IBD, such as irritable bowel syndrome (IBS) or hemorrhoids.…”
Section: Introductionmentioning
confidence: 99%
“…IBD has been associated with poor quality of life and extensive morbidity and often results in complications requiring hospitalizations and surgical procedures (2)(3)(4). Most previous studies of IBD have used administrative claims data or data collected from limited geographic areas to demonstrate increases in estimated prevalence of IBD within the United States (5,6). Few national prevalence estimates of IBD among adults based on large, nationally representative data sources exist, and those that do tend to be based on older data.…”
mentioning
confidence: 99%